Prosecutorial Decisionmaking and Discretion in the Charging Function - Gershman, Bennett L. (2011)
A prosecutor’s charging decision is the heart of the prosecution function. The charging decision involves an extraordinary exercise of discretionary power that is unreviewable. As a result, the decision is difficult to guide except in the broadest terms. The proposed revisions to the ABA’s Criminal Justice Standards for the Prosecution Function attempt to address several key issues that inform the charging decision, by broadening the language of several provisions of the current Standards as well as adding several new provisions. To be sure, the proposed Standards significantly change the current Standards with respect to the proper factors and considerations affecting a prosecutor’s charging decision. Nonetheless, it is unclear whether these Standards purport to establish ethical guidelines for prosecution, or merely guidelines for a prosecutor’s exercise of judgment and policy in the charging function. This Article assesses the extent to which the proposed Standards cover several charging issues effectively, inadequately, or at all. Specifically, this Article focuses on (1) the retention and modification of the probable cause standard for filing charges; (2) the differing Standards for filing and maintaining charges; (3) the role of innocence in the charging decision; (4) discretionary factors in the charging decision; (5) improper considerations in the charging decision; (6) the role of race and community pressure; (7) the issue of filing multiple charges—so-called “overcharging”—and (8) the Standard for actions premised on a defendant’s agreement not to sue